The Battle Of Chernobyl - Blankenship, Steve (Teaching History: A Journal of Methods, 2008)
In the early morning hours of 26 April 1986, in the Ukrainian city of Pripyat, a reactor at the Chernobyl nuclear power plant exploded. Soviet technicians at the No. 4 unit, paralyzed by the fear of responsibility and failure (though not of death), delayed to inform the highest authorities, including General Secretary Mikhail Gorbachev, until the surrounding population and countryside had been saturated with high levels of deadly radioactivity that has rendered the region around the abandoned city uninhabitable now and into the future.1